PERAN UNITED NATIONS WOMEN (UN WOMEN) DALAM MENGATASI GENDER-BASED VIOLENCE (GBV) DI INDIA: STUDI KASUS PEREMPUAN KASTA DALIT TAHUN 2020-2021 - Zega, Nur Afni Waljannah; Nizmi, Yusnarida Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study discusses the role of United Nations Women in addressing genderbased violence in India, with a specific focus on Dalit women during the 2020–2021 period. The background of this research is rooted in the high incidence of genderbased violence in India, driven by patriarchal norms and the caste system, resulting in Dalit women facing intersectional, double discrimination due to their gender and social status, which exacerbates their vulnerability to physical, sexual, and psychological violence The research method is a qualitative case study with a deductive-descriptive approach. Data were collected by study library research, reviewing of books, journals, official reports, as well as UN Women’s documents and publications. The theoretical frameworks of constructivist and theory of international organizations as developed by Michael Barnett and Martha Finnemore, with the level of analysis focused on international organizations. This research show that UN Women implemented various strategic programs in India, such as advocacy initiatives, and Gender Responsive Budgetin gwhich successfully raised public awareness, empowered women economically, strengthened gender-responsive policies, and built partnerships with civil society organizations. However, challenges such as limited funding, cultural barriers, and weak law enforcement against perpetrators of gender-based violence (GBV) remain to be addressed. Keywords: Gender-Based Violence, Dalit Caste, India, UN Women